FtsZ-less prokaryotic cell division as well as FtsZ- and dynamin-less chloroplast and non-photosynthetic plastid division - Miyagishima, Shin-ya; Nakamura, Mami; Uzuka, Akihiro; Era, Atsuko (Frontiers in Plant Science, 2014)
The chloroplast division machinery is a mixture of a stromal FtsZ-based complex descended from a cyanobacterial ancestor of chloroplasts and a cytosolic dynamin-related protein (DRP) 5B-based complex derived from the eukaryotic host. Molecular genetic studies have shown that each component of the division machinery is normally essential for normal chloroplast division. However, several exceptions have been found. In the absence of the FtsZ ring, non-photosynthetic plastids are able to proliferate, likely by elongation and budding. Depletion of DRP5B impairs, but does not stop chloroplast division. Chloroplasts in glaucophytes, which possesses a peptidoglycan (PG) layer, divide without DRP5B. Certain parasitic eukaryotes possess non-photosynthetic plastids of secondary endosymbiotic origin, but neither FtsZ nor DRP5B is encoded in their genomes. Elucidation of the FtsZ- and/or DRP5B-less chloroplast division mechanism will lead to a better understanding of the function and evolution of the chloroplast division machinery and the finding of the as-yet-unknown mechanism that is likely involved in chloroplast division. Recent studies have shown that FtsZ was lost from a variety of prokaryotes, many of which lost PG by regressive evolution. In addition, even some of the FtsZ-bearing bacteria are able to divide when FtsZ and PG are depleted experimentally. In some cases, alternative mechanisms for cell division, such as budding by an increase of the cell surface-to-volume ratio, are proposed. Although PG is believed to have been lost from chloroplasts other than in glaucophytes, there is some indirect evidence for the existence of PG in chloroplasts. Such information is also useful for understanding how non-photosynthetic plastids are able to divide in FtsZ-depleted cells and the reason for the retention of FtsZ in chloroplast division. Here we summarize information to facilitate analyses of FtsZ- and/or DRP5B-less chloroplast and non-photosynthetic plastid division.